دراسة تأثير زراعة شتول بندورة مطعمة على أصول مختلفة في النمو والإنتاج تحت ظروف الزراعة المحمية - حميدان مروان; شيخ سليمان نصر; ابراهيم علاء (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال عامي 2010-2011 في قرية بستان الباشا- جبلة- اللاذقية, وتمت دراسة نمو وإنتاج نباتات هجين البندورة هدى F1 المطعمة على 3 أصول هجينة: Multifort و ES 30502 و Spirit بالإضافة إلى النباتات غير المطعمة (الشاهد). أظهرت النتائج تفوق النباتات المطعمة على الأصل ES 30502 معنوياً على باقي المعاملات في طول النبات ونسبة العقد, وأدى التطعيم إلى زيادة قطر ساق النباتات مقارنةً بالشاهد, كما أثر التطعيم في زيادة عدد الأوراق المتشكلة؛ وتفوقت النباتات المطعمة على الأصل ES 30502 معنوياً في عدد العناقيد الزهرية كما تفوقت النباتات المطعمة على الأصل Multifort معنوياً في عدد الأزهار الكلي على كلٍّ من الشاهد والنباتات المطعمة على الأصل Spirit. وتفوقت جميع النباتات المطعمة في كمية الإنتاج المبكر والكلي مقارنةً بالشاهد, وتباين نمو وإنتاج النباتات حسب الأصل المستخدم في التطعيم. This research was conducted during 2010-2011 in Bostan Al-basha - Jableh-Lattakia. Growth and yield of Tomato Plants (Hybrid Huda F1) grafted on 3 hybrid rootstocks: Multifort, ES 30502 and Spirit were studied and compared with the growth and production of non-grafted plants (control). The results showed that grafted plants on ES 30502 were significantly superior to other treatments in plant height and fruit set percentage. Plant diameter increased by grafting compared to the control. Also grafting has a positive influence on the number of leaves. Grafted plants on ES 30502 were significantly superior in the number of clusters per plant and grafted plants on Multifort were superior in the number of flowers per plant to both the control and grafted plants on Spirit. Grafted plants were superior in earliness and total production compared to the control. The growth and production of grafted plants varied by rootstock.